DISCURSIVE ANALYSIS OF THE INFORMATION GENRE OF THE INTERNET MEDIA - Teshabaeva Dilfuza Muminovna (Western European Studies, 2023)
This study employs discursive analysis to explore the intricacies of the information genre within Internet media. Findings reveal a dynamic interplay of linguistic and visual elements shaping contemporary online communication, emphasizing the rapid dissemination of news, the influence of user-generated content, and the evolving role of multimedia. The study contributes valuable insights for media practitioners navigating the complex realm of Internet media and enriches theoretical frameworks in discursive analysis. Implications for inclusivity in content creation processes and recognition of power dynamics embedded in discursive strategies are emphasized. Reflecting on limitations, the study suggests future research avenues including investigations into the impact of emerging technologies on the information genre and longitudinal studies tracking the evolution of discursive patterns over time. In essence, this study serves as a foundational exploration into the intricate tapestry of the information genre within Internet media, offering a glimpse into the dynamic world of online communication
Keywords: Internet media; information genre; discursive analysis; online communication